RESEARCH OF THE RELATIONSHIP BETWEEN EXISTENTIAL ANXIETY AND THE SENSE OF PERSONALITY’S EXISTENCE - Popovych, Ihor; Kononenko, Oksana; Kononenko, Anatoliy; Stynska, Viktoriia; Kravets, Nadia; Piletska, Liybomyra; Blynova, Olena (Revista Inclusiones, 2020)
The purpose of the empirical study is to establish relationships between existential anxiety and the sense of personality’s existence (n=60). It is noted that anxiety is the most important element of human existence, the natural reaction of man to uncertainty. A fundamental analysis of the meaning of human existence is presented. The correlation between existential anxiety and the sense of personality’s existence (p≤.05; p≤.01) has been empirically investigated and established, which substantially supplemented the existing knowledge of the studied phenomena. The relationship between the level of the Self-estimation of Personal Anxiety (SPA) and the level of General Awareness of Life (GAL) is stablished and described. The presence of high feedback correlation -.829; p≤.01) was statistically confirmed. The results of the study are summarized and the assumption is made that the awareness of life is a sign of human mental health. It is noted that a high level of anxiety should be considered as a higher possibility of revealing the potential purpose of a person. It is emphasized that living and experiencing one’s existence means learning about the purpose in the world that does not guarantee its comprehension.